A threefold superstructure of the anti‐epileptic drug phenytoin sodium as a mixed methanol solvate hydrate. Issue 9 (5th August 2019) - Shah, Harsh S.; Chaturvedi, Kaushalendra; Zeller, Matthias; Bates, Simon; Morris, Kenneth
Abstract : Phenytoin sodium crystallizes as a threefold modulated crystal structure that consists of a supercell made up of three close‐to‐identical repeat units. Abstract : Phenytoin sodium, a salt of 5, 5‐diphenylimidazolidine‐2, 4‐dione, or phenytoin, is commercially available in various dosage forms for its anti‐epileptic properties to treat and prevent seizures. The title compound, poly[aquatris(μ3 ‐4, 4‐diphenyl‐2, 5‐dioxoimidazolidin‐1‐ido)trimethanoltrisodium(I)], [Na3 (C15 H11 N2 O2 )3 (CH4 O)3 (H2 O)1.08 ] n, a methanol solvate and hydrate of phenytoin sodium, forms a modulated crystal structure that consists of a supercell made up of three close‐to‐identical repeat units. Each of the basic fragments consists of one phenytoin anion, a sodium cation, and either a methanol, or a methanol and a water molecule coordinated to the sodium ion, yielding a formula unit of Na(C15 H11 N2 O2 )(CH3 OH) x (H2 O) y for each of the three segments ( x, y = 0 or 1; x  +  y = 1 or 2). Modulation along the b axis is introduced due to the presence or absence of water or methanol molecules at sodium and by the alternating torsion angles of one of the two phenytoin phenyl rings. Individual segments within the asymmetric unit are linked by covalent Na—O and Na—N bonds, with each sodium ion coordinated to one anionic amide N atom and three keto O atoms. The Na—N and one of the Na—O bonds connect (C15 H11 N2 O2 )·Na units along the modulation direction, creating an infinite [(C15 H11 N2 O2 )·Na] chain that is further stabilized by intramolecular N—H…O hydrogen bonding parallel to [010]. The second Na—O bond connects this chain with a symmetry‐equivalent copy of itself created by a screw‐axis operation, yielding double strands of [(C15 H11 N2 O2 )·Na] chains. Two of these double strands, propagating in opposite directions, constitute the content of the unit cell. Neighboring double strands are connected with each other to form layers perpendicular to the a axis, tethered together via O—H…O hydrogen bonds involving the water and methanol molecules. In addition to modulation, each of the repeat units also exhibits disorder of the modulated segments. Phenyl rings of each repeat unit are rotationally disordered, and sodium‐coordinated methanol and water molecules are also positionally disordered and/or partially occupied. The solvated structure reported here, while not matching the patterns reported for any of the known forms of phenytoin sodium, does provide a first insight into the complications and complexities involved in resolving the structure of anhydrous phenytoin sodium.